Three-dimensional analysis of the anterior loop of the inferior alveolar nerve in relation to the growth pattern of the mandibular functional subunit - Seungkyu Yoon; Jae-Young Kim; Cheol-Hee Jeong; Jengbin Park; Jong-Ki Huh; Kwang-Ho Park (SpringerOpen, 2018)
Abstract Background The purpose of the present study was to investigate the differences in the position and shape of the anterior loop of the inferior alveolar nerve (ALIAN) in relation to the growth pattern of the mandibular functional subunit. Methods The study was conducted on 56 patients among those who had undergone orthognathic surgery at the Gangnam Severance Hospital between January 2010 and December 2015. Preoperative computerized tomography (CT) images were analyzed using the Simplant OMS software (ver.14.0 Materialise Medical, Leuven, Belgium). The anterior and inferior lengths of ALIAN (dAnt and dInf) and each length of the mandibular functional subunits were measured. The relationship between dAnt, dInf, and the growth pattern of the mandibular subunits was analyzed. Results The length of the anterior portion of ALIAN (dAnt) reached 3.34 ± 1.59 mm in prognathism and 1.00 ± 0.97 mm in retrognathism. The length of the inferior portion of ALIAN (dInf) reached 6.81 ± 1.33 mm in prognathism and 5.56 ± 1.34 mm in retrognathism. The analysis of Pearson's correlation coefficiency on all samples showed that the lengths of functional subunits were positively correlated with the loop depth. The length of the symphysis area in prognathic patients was positively correlated with the anterior loop depth (p = 0.005). Conclusions Both the anterior and inferior length of ALIAN are longer in prognathic patients. Especially, it seems to be associated with the growth of the symphysis area.